1987
DOI: 10.1002/bscb.19870961014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Topsentin‐A, A Bisindole Alkaloid of the Marine Sponge Topsentia genitrix

Abstract: ring sponge TOp8mtM g e n i t r k , has been achieved starting from 3-acetylindole. The synthesis of topsentin-A, a bisindole alkaloid isolated from the ma- Recently, we reported the isolation from the marine sponge T o p e e n t i a g e n i t r kof three related basic compounds, topsentin-AU), -el(?) and -B2(2) pertaining to a new type of bisindole alkaloids. The structure determinations were based on their spectral properties and, in particular, on homo-and heterocorrelated 2D NWR experiments"). These deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…20 and 21. Our proposed synthesis of the desired α-oxo-1H-indole-3-thioacetamides 11-14 required the prior synthesis of carbonylnitrile precursors (27)(28)(29)(30). Although Jonosik et al 32 reported a method to synthesize variably functionalized indolyl-3-carbonylnitriles over three steps from indole (31), we opted for the one pot three step method originally developed by Hogan and Sainsbury, 33 and subsequently frequently utilized by Horne and co-workers.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…20 and 21. Our proposed synthesis of the desired α-oxo-1H-indole-3-thioacetamides 11-14 required the prior synthesis of carbonylnitrile precursors (27)(28)(29)(30). Although Jonosik et al 32 reported a method to synthesize variably functionalized indolyl-3-carbonylnitriles over three steps from indole (31), we opted for the one pot three step method originally developed by Hogan and Sainsbury, 33 and subsequently frequently utilized by Horne and co-workers.…”
Section: Resultsmentioning
confidence: 98%
“…We shed new light on known syntheses of -bromo-1-(1H-indol-3-yl)-ethanones (15)(16)(17)(18) and indolyl-3-carbonylnitriles (27)(28)(29)(30) and in the process have gained new mechanistic insight into these useful transformations. Finally, we have confirmed the pivotal contribution of the piperazine-2-one and imidazole rings to the MRSA PK inhibition of cis-3,4-dihydrohamacanthin B and bromodeoxytopsentin respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…46 This analogous condensation strategy has been used on two further occasions by Tsujii et al 25 and Miyake et al 47 While this cyclic condensation approach is both an elegant and relatively uncomplicated method of synthesizing topsentin analogs, it lacks the regiospecificity necessary for an efficient synthesis of those analogs with differently substituted indole moieties.…”
Section: Synthesismentioning
confidence: 97%
“…Bartik recognized that all three compounds exist as a mixture of slowly interconverting imidazole tautomers in neutral solution, resulting in the doubling of resonances in the 1 H and 13 C NMR spectra of these compounds. 24 The isolation of this initial cohort of three topsentin metabolites was followed by the synthesis of isotopsentin (45) and hydroxytopsentin (46) and the isolation of 4,5-dihydro-6 00 -deoxybromotopsentin (47) (later renamed spongotine A) 26 collected in the Caribbean. 25 In the literature, the trivial name spongotine has been generally reserved for dihydrotopsentin analogs (mostly, but not exclusively, isolated from the genus Spongosorites) in which an acylimidazoline moiety replaces the acylimidazole moiety characteristic of topsentins.…”
Section: Isolation and Bioactivitymentioning
confidence: 99%